Excellence in human resources management - McFee, Thomas S.
The author spent a great deal of time talking about various aspects of the career-political debate. He further deseribes that the effective corear political relations are one of the keys to both individual and organizational success in the federal government. Excellence in human resource management starts at the top, with career-political harmony of both individual and organization and serve as a model for excellence in human resource management up and down and across the organization, as well as throughout generations of public servants to come. Hence our citizens deserve no loss.
Keywords: Legislators; Political Executives; Human Resources Management; Civil Service; Civil Service and Legislators